2007
DOI: 10.1117/1.2749730
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved Mueller matrix study of light scattering by B-cells at three wavelengths of 442, 633, and 850 nm

Abstract: Angle-resolved signals of polarized light scattered by biological cells provide rich information on cell morphology. Quantitative study of these signals can lead to new methods to develop and improve high-throughput instrumentation for cell probing such as scattering-based flow cytometry. We employ a goniometer system with a photoelastic modulation scheme to determine selected Mueller matrix elements of B-cell hydrosol samples. The angular dependence of S(11), S(12), and S(34) is determined from the scattered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…In fact, it can be readily observed that apoptotic cells distribute differentially from the viable cells in a scatter plot of the angularly integrated side scatters (SSC) versus the forward scatters (FSC) obtained with the FCM assay [18,19]. These results suggest some strong correlations between the morphological variations in apoptotic cells relative to the viable cells and spatial distribution of scattered light, which are consistent with the experimental and modeling studies on light scattering by biological cells of different morphology in general [15][16][17][20][21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 82%
“…In fact, it can be readily observed that apoptotic cells distribute differentially from the viable cells in a scatter plot of the angularly integrated side scatters (SSC) versus the forward scatters (FSC) obtained with the FCM assay [18,19]. These results suggest some strong correlations between the morphological variations in apoptotic cells relative to the viable cells and spatial distribution of scattered light, which are consistent with the experimental and modeling studies on light scattering by biological cells of different morphology in general [15][16][17][20][21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 82%
“…Consequently, all information about the scatterer properties that can be extracted from scattering measurements is contained in the elements of the Mueller matrix. Therefore, different techniques and instruments have been developed to measure these elements (Ding et al, 2007;Hull, Shepherd, & Hunt, 2004;Hunt & Huffman, 1973;Hunt, Quinby-Hunt, & Shepard, 1998;Perry, Hunt, & Huffman, 1978). These techniques typically utilize polarization modulated scattering (PMS) to simultaneously measure multiple elements of the Mueller matrix.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in the case of diffraction imaging to record spatial distribution of coherent light scattered by single cells with a flow cytometer. Previous studies by different groups, including ours, have developed simplified OCMs of constant or varying RI within a cell and/or its individual organelles built by spheres or spheroids [4,37,38], mathematical surfaces [39], reconstruction from confocal image stack data for nucleus only [10,33,40] or Gaussian random sphere models for nucleus and mitochondria [41,42]. These models may be sufficiently accurate for investigation of certain aspects of scattered light distributions such as angularly (1D) or spectroscopically resolved measurements [43].…”
Section: Discussionmentioning
confidence: 99%